2012
DOI: 10.4067/s0718-16202012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of soil organic matter in tropical soils with near-infrared spectroscopy (NIRS) and chemometrics

Abstract: A. Jarquín-Sánchez, S. Salgado-García, D.J. Palma-López, and W. Camacho-Chiu. 2012. Analysis of organic matter in tropical soils with near-infrared spectroscopy (NIRS) and chemometrics. Cien. Inv. Agr. 39(2): 387-394. The objective of this study was to predict the concentration of soil organic matter (SOM) in tropical soils using near-infrared spectroscopy (NIRS) for samples measured within a polyethylene bag and without a bag. One hundred and fifty six soil samples from the humid tropics of Tabasco, Mexico wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The concentrations of Ca found in this study were lower than those found by Cardenas et al (2013) in three different soil series (including Andisols and Ultisols) in southern Chile. Mg concentration was similar in both soil types but lower than the values reported by Debaene et al (2010), Jarquín-Sánchez et al (2012), and Cardenas et al (2013) for Polish, Mexican, and volcanic Chilean ash soils, respectively. This difference is probably explained by the fact that the data of the present study correspond to fertilized and non-fertilized soils, while the studies mentioned before included Mg fertilizer application.…”
Section: Chemical Soil Characterizationsupporting
confidence: 45%
“…The concentrations of Ca found in this study were lower than those found by Cardenas et al (2013) in three different soil series (including Andisols and Ultisols) in southern Chile. Mg concentration was similar in both soil types but lower than the values reported by Debaene et al (2010), Jarquín-Sánchez et al (2012), and Cardenas et al (2013) for Polish, Mexican, and volcanic Chilean ash soils, respectively. This difference is probably explained by the fact that the data of the present study correspond to fertilized and non-fertilized soils, while the studies mentioned before included Mg fertilizer application.…”
Section: Chemical Soil Characterizationsupporting
confidence: 45%
“…Due to the broad and overlapping bands, VIS-NIR spectra contained fewer absorption than the SWIR range, which can be more difficult to interpret [43]. According to the literature, these wavelengths are where the concentrations of elements in the soil are located [44]. In the same way as [45], the spectra showed absorption bands at wavelengths between 1400 and 2500 nm, related to the chemical bonds of the soil elements.…”
Section: Spectral Signatures and Main Variablesmentioning
confidence: 99%
“…Moreover, the VIS-NIR method has great potential for simultaneous estimation of a variety of soil properties including, e.g., cation exchange capacity, pH, exchangeable bases, extractable phosphorus, soil texture [ 29 , 30 ], or presence of polycyclic aromatic hydrocarbons [ 31 ]. However, most of the studies focused mainly on total SOC concentration [ 28 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%